Strategi Holistik Retensi Guru Di Sekolah Islam Terpadu: Studi Kasus SMPIT Al Itqon Bogor - Bayan Rahman; Nur Atik Azkiyah; Hasyim Asy'ari; Armai Arief (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Teacher retention is a key factor in maintaining the stability and quality of education, especially in the integrated Islamic school environment. Challenges in retaining experienced teachers often arise due to welfare dynamics, workload, and career development needs. This study aims to analyze the teacher retention strategy implemented at SMPIT Al Itqon Bogor as an effort to create sustainability in the quality of education. This study uses a descriptive qualitative research method of data collection techniques through interviews with school principals, vice principals and human resource development coordinators as well as permanent teachers with a minimum service period of five years. The results of the study show that there are five main strategies in retaining teachers, namely sustainable development of professional competencies, providing financial and non-financial welfare, regular spiritual coaching, creating a conducive work environment, and strengthening managerial communication. The retention strategy implemented is holistic by integrating professional aspects, welfare, spirituality, and organizational culture based on Islamic values. The success of teacher retention at SMPIT AL ITQON Bogor is the result of the synergy of various dimensions that strengthen each other, as well as becoming a model of human resource management that is relevant for the development of other integrated Islamic educational institutions. The novelty of this research lies in the teacher retention model based on the integration of professional and spiritual values in the context of integrated Islamic schools, which has not been widely studied in previous research